«Русская идея» как модель цивилизационного бытия коллизии процесса воплощения и идентификации - Муза, Д.Е.; Алиева, О.Г. (Культура народов Причерноморья, 2006)
This article is devoted to the problem of realization of the "russian idea" in history as a model of its civilized existence; to definition the spiritual orientations of the Russian civilization. The diversity of interpretation of the valuable priorities as creation of the Russian civilization history are developed here. Данная статья посвящена проблеме реализации "русской идеи" в истории, как модели цивилизационого бытия; определению духовного своеобразия русской цивилизации, исходя из интерпретации этой базисной модели. Ця стаття присвячена проблемі реалізації "руської ідеї" як моделі цивілізаційного буття; виявленню духовної самобутності руської цивілізації, відповідно до інтерпретації цієї базової моделі.